Engaging the next generation: authoritarian regimes and their young diaspora - Wackenhut, Arne F.; Orjuela, Camilla (European political science, 2023)
Recent scholarship on diaspora engagement and transnational repression has investigated how authoritarian regimes seek to engage, govern and control their diasporas. Recognizing that diasporas are diverse and that homeland states thus devise different strategies in relation to different groups, this research has—to a large extent—focused on the varied positions held by regime supporters and dissidents. Inter-generational differences, however, have not been studied in this context. Drawing on established frameworks theorizing extraterritorial authoritarian practices, this article explores the ways in which second-generation diaspora—or diaspora youth—is either included as subjects, patriots and clients, or excluded as outlaws and traitors by authoritarian regimes. Drawing on the literature on transnationalism and second-generation migrants, and using examples from empirical cases, we argue that the skills, resources and multi-sited embeddedness of the second-generation diaspora can make them particularly interesting targets for transnational engagement—or repression. We draw attention to specific strategies for mobilizing the support of diaspora youth, but also note that some techniques to control or repress extraterritorial subjects are less efficacious in relation to this generation.